2018
DOI: 10.3390/risks6020038
|View full text |Cite
|
Sign up to set email alerts
|

Credit Risk Analysis Using Machine and Deep Learning Models

Abstract: Due to the advanced technology associated with Big Data, data availability and computing power, most banks or lending institutions are renewing their business models. Credit risk predictions, monitoring, model reliability and effective loan processing are key to decision-making and transparency. In this work, we build binary classifiers based on machine and deep learning models on real data in predicting loan default probability. The top 10 important features from these models are selected and then used in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
96
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(102 citation statements)
references
References 29 publications
(27 reference statements)
6
96
0
Order By: Relevance
“…The obtained analytical information is used to simulate risk analysis processes based on machine learning algorithms. [13] Curators of credit institutions use a number of criteria by which one can assess the presence of the threat of bankruptcy. A significant number of factors taken into account when choosing a criterion and evaluating its significance makes it difficult to obtain a guaranteed objective solution.…”
Section: Suggestions and Recommendationsmentioning
confidence: 99%
“…The obtained analytical information is used to simulate risk analysis processes based on machine learning algorithms. [13] Curators of credit institutions use a number of criteria by which one can assess the presence of the threat of bankruptcy. A significant number of factors taken into account when choosing a criterion and evaluating its significance makes it difficult to obtain a guaranteed objective solution.…”
Section: Suggestions and Recommendationsmentioning
confidence: 99%
“…When it comes to the methodological framework to predict defaults and credit risk, the study by Halteh et al (2018) developed cutting-edge tree-based stochastic models to model credit risk. Addo et al (2018) built binary classifiers based on machine and deep learning models on real data to predict loan default probability. The performance of classification was tested on separate data.…”
Section: Data and Modeling Approachmentioning
confidence: 99%
“…Newly developed data mining techniques and advancements in computational intelligence capabilities have been applied to build intelligent information systems for modeling complex, dynamic, and multivariate nonlinear systems (Nayak et al, 2018;Adhikari & Agrawal, 2014). In particular, soft computing methodologies have been applied successfully to areas such as data classification (Alatas, 2011;Alatas, 2012;Nayak et al, 2015), financial forecasting (Nayak et al, 2018), credit scoring (Addo et al, 2018;Tomczak & Zięba, 2015;Chow, 2018), portfolio management (Xu et al, 2011a), business failure prediction, and risk level evaluation (Daubie & Meskens, 2002;Chandra et al, 2009), and they have been found to produce significantly improved results. ANNs have proven to be an effective modeling procedure in stock market forecasting when the input-output mapping contains both regularities and exceptions (Nayak et al, 2018;Zhang, 2003;Adhikari & Agrawal, 2014;Gu et al, 2018;Board, 2017).…”
Section: Introductionmentioning
confidence: 99%